(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Awareness about diabetic eye complications and regular eye examinations plays an important role in avoiding blindness. Objective:To assess the level of awareness and knowledge regarding diabetic ocular diseases among diabetic patients attending Aden Diabetic Center at Al-Gamhoria Teaching Hospital in Aden. Method:This is a cross sectional study including a sample of 182 diabetic patients attending this center during the period from January – March 2013. To achieve the objectives of the study, a closed-ended questionnaire including different variables related to diabetic patients’ awareness supplied to each patient. The authors filled in the questionnaire during interviews with the patients. Result:The results showed that 109 patients were females and 73 were males with a mean age 53 years and half of the patients were illiterates. Of the total 182 respondents, 157 (86.3%) had variable awareness and knowledge of ocular complications of diabetes mellitus. From those 157 respondents, 124 (79%) had awareness of blindness as an ocular diabetic complication. Awareness of diabetic complications affecting other organs was 93.6%. Awareness regarding the importance of controlling issues caused by diabetes mellitus and its impact on preventing eye complications as well as other body organs was 73.9%. About 36.8% of respondents never visited eye specialists. Medical staff together with the media was the main source of information about eye diseases. Conclusion:The majority of patients was aware of diabetes mellitus complications and had knowledge of cataract, glaucoma, and retinopathy as the most known ocular complications. Key words:Awareness, eyes, diabetes mellitus, complications.